Interesting images: Multiple coronary artery aneurysms - Jonathon M Howard; Omar Viswanath; Alfredo Armas; Orlando Santana; Gerald P Rosen (Annals of Cardiac Anaesthesia, 2017)
We present the case of a 65-year-old male who presented with stable angina and dyspnea on exertion. His initial workup yielded a positive treadmill stress test for reversible apical ischemia, and transthoracic echocardiogram demonstrated impaired systolic function. Cardiac catheterization was then performed, revealing severe atherosclerotic disease including multiple coronary artery aneurysms. As a result, the patient was advised to and subsequently underwent a coronary artery bypass graft. This case highlights the presence of multiple coronary artery aneurysms and the ability to appreciate these pathologic findings on multiple imaging modalities, including coronary angiogram, transesophageal echocardiography, and direct visualization through the surgical field.